2012
DOI: 10.1039/c1cs15169j
|View full text |Cite
|
Sign up to set email alerts
|

Host–guest sensing by calixarenes on the surfaces

Abstract: The present critical review reports on recent developments of optical nanoparticles based on the association of gold, silver, silica and quantum dots and calixarenes. These hybrid organic-inorganic compounds characterized by a thick organic layer self-assembled on the surface of a core of mineral surface atoms take advantage of the supramolecular recognition of luminescent calixarenes to fabricate nanodevices of nanoparticle size, capable of detecting metal cations, polyaromatic hydrocarbons and pesticides. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
280
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(282 citation statements)
references
References 129 publications
2
280
0
Order By: Relevance
“…This original concept uses rigid tetrapodant calix [4]arenes 33 as building blocks to form robust, closely packed and stable monolayers that can be postfunctionalized. Immobilization of calixarenes onto a surface by self-assembly techniques 34 is classically achieved by anchoring the small rim of the calixarenes onto the substrate through their phenol or thiophenol functions. In contrast, our strategy relies on the large rim grafting of calix [4]arenes, thanks to the diazonium coupling route, whereas the small rim is used for the introduction of spatially controlled postfunctionalizable groups.…”
mentioning
confidence: 99%
“…This original concept uses rigid tetrapodant calix [4]arenes 33 as building blocks to form robust, closely packed and stable monolayers that can be postfunctionalized. Immobilization of calixarenes onto a surface by self-assembly techniques 34 is classically achieved by anchoring the small rim of the calixarenes onto the substrate through their phenol or thiophenol functions. In contrast, our strategy relies on the large rim grafting of calix [4]arenes, thanks to the diazonium coupling route, whereas the small rim is used for the introduction of spatially controlled postfunctionalizable groups.…”
mentioning
confidence: 99%
“…2.). The association constants and the optical spectroscopic data for DSS and its AP6 complex are collected in Table 1, and compared to the respective data for the complexes of DSS with  cyclodextrin, -CD•DSS [61], -cyclodextrin, -CD•DSS2 [62] and cucurbit [7]uril, CB7•DSS [6]. The large signal modulation and the optimal association constant indicated that this system is suitable for FID purposes.…”
Section: Complexation Of Dss With Ap6mentioning
confidence: 99%
“…These changes are usually more significant than the effects observed in direct sensing that makes FID assays more desirable. The macrocyclic components in the majority of these systems are cyclodextrins [5], calixarenes [6][7][8] and cucurbiturils [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[1] An enhanced interest in this promising class of macrocyclic compounds is due to wide opportunities of their practical use. [2] Indeed, calixarenes proved to be effective receptors for selective extraction of metal ions, [3] catalysts, [4] chemosensors, [5,6] transmembrane ion transporters, [7,8] materials for nonlinear optics, [9] biologically active substances, [10] etc. [11] The structural organization of calixarenes has an effect on their complexing properties.…”
Section: Introductionmentioning
confidence: 99%